How rural coworking hubs can facilitate well-being through the satisfaction of key psychological needs. (November 2021) - Merrell, Ian; Füzi, Anita; Russell, Emma; Bosworth, Gary
Once considered an urban phenomenon, rural enterprise hubs (REH) and rural coworking spaces (RCWS) are now increasing in popularity to support entrepreneurial rural communities. Whilst previous research has examined economic and community benefits, a focus on well-being benefits has been overlooked. Framed by self-determination theory, this empirical research investigates whether rural coworking is reported to enhance user's well-being by fulfilling key psychological needs for autonomy, competence and relatedness. By applying a well-being focus, we found that potential key drivers of rural coworking uptake and durability could be elucidated, in terms of these three needs. In addition, we identified another category of well-being that was fulfilled through engagement with RCWS and REH – namely – 'communion with nature'. We suggest that considerations of well-being are important to understand how rural coworking can attract and sustain local workers and suggest a future research agenda to further conceptualise well-being effects.